2011
DOI: 10.2134/jeq2011.0040
|View full text |Cite
|
Sign up to set email alerts
|

Forest Restoration Potentials of Coal‐Mined Lands in the Eastern United States

Abstract: The Appalachian region in the eastern United Sates is home to the Earth's most extensive temperate deciduous forests, but coal mining has caused forest loss and fragmentation. More than 6000 km in Appalachia have been mined for coal since 1980 under the Surface Mining Control and Reclamation Act (SMCRA). We assessed Appalachian areas mined under SMCRA for forest restoration potentials. Our objectives were to characterize soils and vegetation, to compare soil properties with those of pre-SMCRA mined lands that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 55 publications
0
57
0
Order By: Relevance
“…If these lands were not used for grazing, however, they could naturally revert to woody vegetation, particularly on sites adjacent to forest (Franklin et al 2012;Skousen et al 2006). Alternatively, sites would often have compacted soils with chemical properties quite different from native soils; this, plus the dense cover of non-native herbaceous vegetation, inhibited establishment of forest cover for decades (Angel et al 2005;Zipper et al 2011a). The Forestry Reclamation Approach (FRA) was developed to address this challenge in the Eastern USA coal region, which is comprised primarily of temperate deciduous forest (Burger et al 2005a;Zipper et al 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…If these lands were not used for grazing, however, they could naturally revert to woody vegetation, particularly on sites adjacent to forest (Franklin et al 2012;Skousen et al 2006). Alternatively, sites would often have compacted soils with chemical properties quite different from native soils; this, plus the dense cover of non-native herbaceous vegetation, inhibited establishment of forest cover for decades (Angel et al 2005;Zipper et al 2011a). The Forestry Reclamation Approach (FRA) was developed to address this challenge in the Eastern USA coal region, which is comprised primarily of temperate deciduous forest (Burger et al 2005a;Zipper et al 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Bradshaw 1983;Pietrzykowski and Krzaklewski 2007;Zipper et al 2011a, b). A large part of post-mining areas in Europe (Knoche 2005;Pietrzykowski and Socha 2011) and in the eastern United States (Zipper et al 2011b;Franklin et al 2012) have been reclaimed to forest. In Poland (Central Europe) the area taken up by industry and mining is estimated at around 45,000 ha, circa 25,000 ha of which has been reclaimed to forestry.…”
Section: Introductionmentioning
confidence: 99%
“…The significantly greater percent fine soil on the GRP plot was most likely caused by the ripping action during the reclamation process, since Miller et al (2010) found that gray sandstone rocks exhibited a high durability in a slake-durability test and were highly resistant to weathering during the freeze-thaw test. Zipper et al (2011b) reported that soils derived from gray sandstone would continue to have a high percentage of coarse fragments as they age and that many hard-grained sandstones have slow decomposition rates. Table 1 for treatment descriptions.…”
Section: Soilmentioning
confidence: 99%